Respuesta :

Answer:

(i) and (iii)

Step-by-step explanation:

for i)

f(x) = [tex]\frac{x^{2}-4}{x+2}[/tex]

     =[tex]\frac{(x+2)(x-2)}{x+2}[/tex]

     =(x-2)

As x =-2

f(x)=-2-2

f(x)=-4

so it is a continuous function

for ii)

from the result of (i) we can deduce the result of second and we see that it is not equal to zero so it is not a continuous function

iii)

f(x)=[tex]\frac{x^{2}+4x+4}{x+2}[/tex]

f(x)=[tex]\frac{(x+2)^{2}}{x+2}[/tex]

f(x)=[tex]\frac{(x+2)(x+2)}{x+2}[/tex]

f(x)=x+2

as x= -2

f(x)=-2+2

f(x)=0

so it is a continuous function

iv) From the result of iii we can deduct that

f(x)=0 because it have the same equation so it is not a continuous function


Answer:

The first and third functions are continuous at x=-2

Step-by-step explanation:

Please, see the attached files.

Thanks.

Ver imagen Professor1994
Ver imagen Professor1994